Extracellular Vesicle lncRNA Metastasis-Associated Lung Adenocarcinoma Transcript 1 Released From Glioma Stem Cells Modulates the Inflammatory Response of Microglia After Lipopolysaccharide Stimulation Through Regulating miR-129-5p/High Mobility Group Box-1 Protein Axis - Yang, Jiankai; Sun, Guozhu; Hu, Yuhua; Yang, Jipeng; Shi, Yijun; Liu, Hongjiang; Li, Chen; Wang, Yuanyu; Lv, Zhongqiang; Niu, Jianxing; Liu, Honglei; Shi, Xuefang; et al. (Frontiers in Immunology, 2020)
Glioma stem cells (GSCs) derived extracellular vesicles (EVs) can mediate the communication between GSCs and microglia. MALAT1 expression in GSCs, EVs, and the supernatant was detected by real-time PCR. The direct targeting between MALAT1 and miR-129-5p, miR-129-5p and HMGB1 were tested with luciferase reporter analysis. The expression and secretion of interleukin (IL)-6, IL-8, and tumor necrosis factor (TNF)-α were determined in lipopolysaccharide-stimulated microglia or miR-129-5p inhibitor transferred microglia exposing to GSCs EVs or EVs derived from siMALAT1 pre-transferred GSCs. MALAT1 was enriched in GSCs EVs compared with GSCs and up-regulated MALAT1 was also observed in microglia upon GSCs EVs incubation. The relative expression and secretion of IL-6, IL-8, and TNF-α in lipopolysaccharide-stimulated microglia were up-regulated in GSCs supernatant group, which could be reversed by DMA (EVs secretion inhibitor) co-administration or si-MALAT1 pre-transfection of GSCs. Luciferase reporter assay testified the direct binding of MALAT1 and miR-129-5p, miR-129-5p and HMGB1, and si-MALAT1 could up-regulate miR-129-5p expression and down-regulate HMGB1 expression in microglia cells. The concentration of IL-6, IL-8, and TNF-α in lipopolysaccharide-stimulated microglia exposing to EVs from siMALAT1 transfected GSCs could be up-regulated by miR-129-5p inhibition. EVs lncRNA MALAT1 released from GSCs could modulate the inflammatory response of microglia after lipopolysaccharide stimulation through regulating miR-129-5p/HMGB1 axis.